The importance of soft skills in the profession of radiology manipulator - ELKHALLADI, Jaouad; ESSAIDI , Jaouad; OUBRIK, Iymane; TOURABI , Mohamed; EL FAHSSI , Mohamed (Revue Internationale du Chercheur, 2024)
Soft skills are non-technical competencies that are very important in interpersonal relations and in work performance in general and in the healthcare sector in particular. This qualitative and descriptive study aims to investigate the importance of soft skills in the profession of radiology manipulator. The results of this study showed that anticipation, cooperation, self-confidence, stress management, problem solving, punctuality, adapting to the unexpected, open-mindedness, the ability to deal with aggressive behaviour and effective communication are the most important soft skills for radiology manipulators. Training and practice can contribute to the development of soft skills. Other studies could be very useful in assessing soft skills for both radiology manipulators and other healthcare professionals.